Increasing Science Knowledge Among High-Risk Student Populations Through a Community College Honors/Service-Learning Program - Ellerton, Sharon; Carmona, Naydu; Tsimounis, Areti (Journal of college science teaching, 2016)
There is an urgent need to increase K-12 science knowledge and STEM (science, technology, engineering, and mathematics) preparedness for college. State and national data suggest a strong correlation between student performance in STEM subjects and student socioeconomic status, race, and ethnicity. Queensborough Community College (QCC) is situated in one of the most ethnically diverse areas in the country. We have developed several service-learning outreach programs in which QCC college students serve as mentors and engage K-12 students in STEM topics outside the classroom. We describe Anatomy & Physiology (A&P) servicelearning/ honors projects through different community partners serving at-risk junior and senior high school students. QCC students prepare and carry out effective activities to convey concepts of human A&P to this younger student audience. Assessments support the effectiveness of our projects as evidenced by pre- and post-quiz scores of K-12 students and positive survey reports. In addition, the QCC Honors students consistently express their satisfaction with the program through their reflection journals.